Adhesion toughness of multilayer graphene films - Joseph D. Wood (Nature Portfolio, 2017)
The reason why the surface adhesion of a graphene monolayer is much greater than that of graphene multilayers remains unclear. Here, the authors build a model to show interlayer sliding and fracture mode mixity cause the decrease in adhesion toughness of multilayer graphene.